2017
DOI: 10.1039/c7ay00099e
|View full text |Cite
|
Sign up to set email alerts
|

Determination of anionic surfactants in real samples using a low-cost and high sensitive solid contact surfactant sensor with MWCNTs as the ion-to-electron transducer

Abstract: Long-life, low-cost and fast-response graphite pencil lead surfactant sensors based on MWCNTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The development of the new ionophores is of crucial importance for the advancement of novel surfactant sensors with better properties. Recently, our group [12,13] and others [14] showed that the increase of the active surface and electrotransfer may be achieved by the employment of the nanomaterials as ionophores that also provide higher signal stability and lifetime. As nonionic surfactants have a negative influence on potentiometric titrations and the end-point detection [15], it is important to investigate the influence of nonionic surfactants on potentiometric curve shape, size and especially, the detection of the end-point.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the new ionophores is of crucial importance for the advancement of novel surfactant sensors with better properties. Recently, our group [12,13] and others [14] showed that the increase of the active surface and electrotransfer may be achieved by the employment of the nanomaterials as ionophores that also provide higher signal stability and lifetime. As nonionic surfactants have a negative influence on potentiometric titrations and the end-point detection [15], it is important to investigate the influence of nonionic surfactants on potentiometric curve shape, size and especially, the detection of the end-point.…”
Section: Introductionmentioning
confidence: 99%
“…† The results obtained with the present method were found to be comparable with that for a multi-walled carbon nanotube (MWCNT) sensor-based potentiometric titration method. 54 For the analytical quality assurance, the calculated F value (sd 1 2 / sd 2 2 ) was found to be less than the tabulated F-value, revealing that there is no signicant difference between the present method and reference method. Similarly, the student t-value calculated (X 1 À X 2 /nVar 1 2 /n + Var 2 2 /n) at the 95% condence level was also found to be less than the tabulated t-value.…”
Section: àmentioning
confidence: 68%
“…The results obtained from the ATR-FTIR analysis of eight commercial product formulations containing AS using the KBr-impregnated paper substrate were compared with that obtained using MWCNTs/potentiometric titration (Table 2). 54 Further, the accuracy of the present method was checked by calculating the recovery percentage (%) of AS and NS. The recovery percentage (%) was evaluated by measuring the concentration of AS and NS in the spiked and non-spiked (blank) commodity and environmental water samples.…”
Section: àmentioning
confidence: 99%
“…The standard solution of anionic surfactant DS (c = 4 × 10 −3 M) was used as a titrant. The PVC liquid membrane, Direct Potentiometric Surfactant Sensor (DPSS), was used as a reference [10]. For determinations in six disinfectant samples, no significant differences were observed between the means of both the DMI-TPB sensor containing plasticizer P1 and the DPSS at the 95% confidence level.…”
Section: Titration Of Pharmaceutical Disinfectantsmentioning
confidence: 99%